Pharmaceuticals in the tropics: A quantitative study measuring changes in quantity of the active ingredient and microbiological growth - Bharath Raman, Hana Morrissey, Patrick Ball (Journal of Applied Pharmaceutical Science, 2017)
Global climate change is challenging for the pharmaceutical industry as it is for all other industries, where they have to select packaging that keep their products stable. The aim of this study was to investigate the effect of a tropical environment on pharmaceutical preparations in repackaged containers using the drug in the original container as control. This study concluded that in a tropical environment, some immediate release medications, underwent significant changes in their physical characteristics, and a less significant loss of efficacy. Bacterial and fungal growth inside and outside packages used in re-packaging and on the tablet surface occurred after four weeks. To improve patient adherence, multiple-dose compartment dose administration aids are used to alleviate the risk of patients’ non-adherence due to the regimen complexity of chronic disease therapy. On discharge, hospitals dispense between three and seven days’ supply of medication, usually in plastic bottles or sometimes plastic bags, as a cost-saving measure. Re-packaging of medications is currently common practice, to personalizes medication for individual patients. This preliminary study demonstrated that products stored in tropical conditions, changed in their characteristics and gained microbial contamination during the process or repacking. Further research is required to fully characterize the problem.
Keywords: Storage conditions, pharmaceuticals stability, microbial growth, temperature and humidity, medications.